Pengaruh Diklat dan Fasilitas Kerja terhadap Kinerja Pegawai dengan Motivasi Sebagai Variabel Intervening pada Kantor Kecamatan Nipah Panjang Kabupaten Tanjung Jabung Timur - Agustinus, Helmi; Sudirman, Sudirman; Hapsara, Osrita (J-MAS (Jurnal Manajemen dan Sains), 2025)
The aim of this research is to analyze the influence of training and work facilities on employee performance with motivation as an intervening variable at the Nipah Panjang District Office, East Tanjung Jabung Regency. This research uses descriptive verification and quantitative methods. The object of this research is the influence of training and work facilities on employee performance with motivation as an intervening variable at the Nipah Panjang District Office, East Tanjung Jabung Regency, with a total sample of 86 people. Data analysis was carried out using the PLS method. The research results show that training and work facilities have a positive and significant influence on employee motivation and performance at the Nipah Panjang District Office, East Tanjung Jabung Regency. Training has a direct effect on employee motivation by 27.9% and on employee performance by 69.3%, with an indirect effect through work motivation of 10.6%. Work facilities have a direct influence on employee motivation by 72% and employee performance by 68.5%, as well as an indirect influence on employee performance through work motivation by 27.3%. Work motivation also has a positive and significant effect on employee performance by 37.9%. Overall, training and work facilities are proven to play an important role in increasing employee motivation and performance through work motivation as an intervening variable.